Effect of Microstructure and Exothermic Reaction on the Thermal Convection in an Enclosure of Nanoliquid with Continuous and Discontinuous Heating from below - Abeer Alhashash (Journal of Engineering)
Effect of continuous and discontinuous external heating and internal exothermic reaction on thermal convection of micropolar nanoliquid is studied in the present work. The liquid in the enclosure is a water-based nanoliquid containing Cu nanoparticles. The governing equations are solved numerically using the iterative finite difference method (FDM). The studied parameters are the material viscosity (0≤K≤6), nanoparticles volume fraction (0.0≤ϕ≤0.2), and the internal heating (0.0≤G≤2.0). It is found that the convective flow acceleration by adding nanoparticles is retarded by the microrotation and the suppression has a great impact on the weak exothermic reaction for both cases. Increasing the internal reaction decreases the heat transfer rate at the hot wall but increases the heat transfer rate at the cool wall for both cases, Newtonian or micropolar nanoliquid.